2020
DOI: 10.3171/2020.9.focus20564
|View full text |Cite
|
Sign up to set email alerts
|

Preparedness and guidelines for neurosurgery in the COVID-19 era: Indian perspective from a tertiary care referral hospital

Abstract: The COVID-19 pandemic has severely impacted healthcare systems globally. The need of the hour is the development of effective strategies for protecting the lives of healthcare providers (HCPs) and judicious triage for optimal utilization of human and hospital resources. During this pandemic, neurosurgery, like other specialties, must transform, innovate, and adopt new guidelines and safety protocols for reducing the risk of cross-infection of HCPs without compromising patient care. In this article, the authors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 48 publications
0
4
0
1
Order By: Relevance
“…10 Many neurosurgical centers have reported a decrease in their outpatient visits as a direct result of the measures taken by the governments. [19][20][21][22] A study by Ferraris et al concluded that the future use of telemedicine in an outpatient setting would provide a viable and safe method for health service delivery during such circumstances, 23 although the application of telemedicine in neurosurgery is still in its infancy. 24 The decrease in workload was subjectively reflected by the neurosurgical residents in terms of increased time spent in conducting research.…”
Section: Discussionmentioning
confidence: 99%
“…10 Many neurosurgical centers have reported a decrease in their outpatient visits as a direct result of the measures taken by the governments. [19][20][21][22] A study by Ferraris et al concluded that the future use of telemedicine in an outpatient setting would provide a viable and safe method for health service delivery during such circumstances, 23 although the application of telemedicine in neurosurgery is still in its infancy. 24 The decrease in workload was subjectively reflected by the neurosurgical residents in terms of increased time spent in conducting research.…”
Section: Discussionmentioning
confidence: 99%
“… The vaccination plan has not been revealed yet officially. [ 13 , 17 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ] Saudi Arabia Regular practice routine without screening for COVID-19 The number of surgical admissions was decreased to about 66% of the number before the pandemic. Priority was according to the urgency of the patients No changes, similar to the pandemic phase.…”
Section: Discussionmentioning
confidence: 99%
“…None of the members of the team developed symptoms suggestive of COVID. All these guidelines were in accordance with the guidelines followed in other national institutes [ 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%